Narrative medicine to highlight values of Italian pain therapists in a changing healthcare system. (September 2014) - Marini, Maria Giulia; Reale, Luigi; Cappuccio, Antonietta; Spizzichino, Marco; Zini, Pierangelo; Amato, Francesco; Mameli, Sergio; Raffaeli, William
SUMMARY : Until 2010 pain management in Italy was only partially covered and no structural and qualitative mapping had ever been realized. The VEDUTA project was designed to provide a tool to unite pain therapists in national cooperation. Quantitative questionnaires and narrative plots were sent to 350 Italian specialists; 184 therapists completed the first section and 87 also wrote their stories. Narratives were analyzed through transactional analysis and emotional intelligence. Overall, results show that a patient-centered approach is common in daily practice, but that bureaucracy is endangering quality of care. This cultural analysis, through both the application of quantitative assessment and narrative plots, provides a useful tool to improve those aspects of the system detrimental to the appropriate management of pain in Italy.